Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/7182324
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Steep-Axis One-Handed Phacoemulsification under the Guidance of a Verion Image-Guided System

Abstract: Purpose. To compare the efficiency and safety of steep-axis one-handed phacoemulsification with steep-axis two-handed phacoemulsification.Patients and Methods. Patients with cataracts underwent steep-axis one-handed (steep-axis one-handed group) or steep-axis two-handed (steep-axis two-handed group) phacoemulsification with a 2.4 mm clear corneal incision (CCI) under the guidance of the Verion Image-Guided System. Intraoperative phacoparameters, such as visual acuity, surgically induced astigmatism (SIA), tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This cross-sectional study comprised patients with cataract and moderate to high astigmatism who received ophthalmologic measurement at the Department of Ophthalmology, Lixiang Eye Hospital of Soochow University, Jiangsu, China, from May 2018 to September 2019. The inclusion criteria included the following: (1) the patient could smoothly complete OPD-Scan III and Pentacam examinations; (2) regular astigmatism of more than 0.75 D;. The exclusion criteria included the following: (1) keratoconus, corneal scar and other corneal diseases; and (2) history of dry eyes, eye trauma, eye surgery, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional study comprised patients with cataract and moderate to high astigmatism who received ophthalmologic measurement at the Department of Ophthalmology, Lixiang Eye Hospital of Soochow University, Jiangsu, China, from May 2018 to September 2019. The inclusion criteria included the following: (1) the patient could smoothly complete OPD-Scan III and Pentacam examinations; (2) regular astigmatism of more than 0.75 D;. The exclusion criteria included the following: (1) keratoconus, corneal scar and other corneal diseases; and (2) history of dry eyes, eye trauma, eye surgery, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, cataract surgery has entered the era of refractive surgery, and the intraoperative correction of corneal astigmatism is a necessary requirement for refractive cataract surgery (RCS) [1]. The precise measurement of keratometry, corneal astigmatism and axis is signi cant in planning RCS, such as identifying the location and with of the clear corneal incision(CCI) [2,3],and calculating the type and axis of Toric intraocular lens (IOL) [4,5]. In addition, calculating the power of IOL power also depend on keratometry [ 6] .At present, there are many devices for measuring keratometry in clinical practice, such as Pentacam, IOL-Master, VERION and so on.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies collected use a size between 2.2 and 3.5 mm (Table 1 ). The arithmetic difference between the preoperative and postoperative corneal astigmatism was below 0.5 D in the 13 retrieved studies, with only three studies (23%) reporting a difference greater than or equal to 0.3 D [ 50 52 ]. Furthermore, only one study reported the percentage of subjects achieving postoperative refractive astigmatism in 0.25 D (34%), 0.50 D (56%), 0.75 D (72%), and 1 D (91%).…”
Section: Astigmatism Correction With Corneal Incisionsmentioning
confidence: 99%